The Effect of Learning Interests on Academic Performance of Secondary School Student - Chen, Zhenglin (Transactions on Social Science, Education and Humanities Research, 2024)
Students' interest in learning and academic performance is not only an important aspect to measure the quality of students, but also the focus of attention in education and teaching. Interest is of great significance to the development of people's learning activities and other aspects. it is one of the driving forces to stimulate students' learning motivation and promote students' learning and development. Therefore, it is of great significance to explore the influence of middle school students' learning interest on academic performance. this paper will analyze the influencing factors of middle school students' learning interest, such as learning environment and learning content, at the same time, it studies the relationship between middle school students' learning interest and academic performance: the relationship between learning interest and classroom performance, learning achievement and students' personal development. On this basis, this paper discusses the influence of learning interest on academic performance, and puts forward some strategies to improve middle school students' learning interest.